Clinical usefulness of the nested polymerase chain reaction in the diagnosis of extrapulmonary tuberculosis Utilidad clínica de la reacción en cadena de la polimerasa anidada para el diagnóstico de tuberculosis extrapulmonar - Guadalupe García-Elorriaga; Carlos Gracida-Osorno; Guadalupe Carrillo-Montes; César González-Bonilla (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE:To evaluate the effectiveness of nested polymerase chain reaction (PCR) for diagnosis of extrapulmonary tuberculosis (ETB), as well as the impact of PCR results on clinical management. MATERIALS AND METHODS:We conducted a study of nested PCR tests in 45 patients and a review of patient hospital files, calculating sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). RESULTS:PCR was positive in 51% of cases; PCR sensitivity for diagnosing TB was 86%, specificity was 79%, PPV was 76%, and NPV was 88%. When solely analyzing urine samples, sensitivity and NPV increased to 100%. PCR exerted an influence on management in 27% of patients. CONCLUSIONS:PCR for rapid diagnosis of extrapulmonary TB has an adequate effect, which improves when performed on urine. The results of PCR exerted an acceptable impact on the clinical management of these patients. OBJETIVO:Evaluar la eficacia de la reacción en cadena de la polimerasa (PCR) anidada para el diagnóstico de tuberculosis extrapulmonar, así como el impacto de sus resultados en el manejo clínico. MATERIAL Y MÉTODOS: Se realizó PCR anidada en 45 pacientes y se llevó a cabo la revisión de expedientes. Se calculó sensibilidad, especificidad, valor predictivo positivo (VPP) y valor predictivo negativo (VPN). RESULTADOS:La PCR fue positiva en 51% de los casos, la sensibilidad fue de 86%, la especificidad de 79%, el VPP de 76% y el VPN de 88%. Al analizar solamente las muestras de orina, la sensibilidad y VPN se incrementaron a 100%. La PCR influyó en el manejo de 27% de los pacientes. CONCLUSIONES:La PCR para el diagnóstico rápido de TB extrapulmonar tiene una eficacia adecuada, la cual mejora cuando se realiza en orina. El resultado de la PCR tuvo un impacto aceptable en el manejo clínico de estos pacientes.